2022
DOI: 10.1002/ccr3.5492
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of upper and lower respiratory infection due to Lophomonas in a post‐kidney transplantation patient

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“… 3 The majority of cases have been reported from Asian countries such as Iran and China. 3 , 4 , 5 , 6 , 7 , 9 , 10 It has been shown that children's immunity is less effective than adults. 13 Furthermore, due to poor hygienic habits, children are more exposed to pathogens in their surroundings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 3 The majority of cases have been reported from Asian countries such as Iran and China. 3 , 4 , 5 , 6 , 7 , 9 , 10 It has been shown that children's immunity is less effective than adults. 13 Furthermore, due to poor hygienic habits, children are more exposed to pathogens in their surroundings.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, for the first time, all lophomoniasis patients were confirmed by a PCR‐based test. 4 The majority of our cases live in urban areas, and the people living there are more exposed to cockroaches due to the high population of these insects. On the other hand, cockroaches are considered the main reservoir host for the Lophomonas parasite.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 The parasite may infect a number of tissues and organs, but clinically, the respiratory tract is the most commonly infected tissue. 2 , 3 Generally, Lophomonas infection causes symptoms (cough, sputum, and shortness of breath) in the respiratory tract. 4 , 5 , 6 It is difficult to distinguish this infection from other common lung infections with similar symptoms, such as pneumonia, bronchitis, or inflammation.…”
Section: Introductionmentioning
confidence: 99%